Structural identification of mouse fecal metabolites of theaflavin 3,3′-digallate using liquid chromatography tandem mass spectrometry - Chen, Huadong (2011)
Black tea consumption has been associated with many health benefits including the prevention of cancer and heart disease. Theaflavins are the major bioactive polyphenols present in black tea. Unfortunately, limited information is available on their biotransformation. In the present study, we investigated the metabolic fate of theaflavin 3,3′-digallate (TFDG), one of the most abundant and bioactive theaflavins, in mouse fecal samples using liquid chromatography/electrospray ionization tandem mass spectrometry by analyzing the MS(n) (n = 1–3) spectra. Four metabolites theaflavin, theaflavin 3-gallate, theaflavin 3′-gallate, and gallic acid were identified as the major mouse fecal metabolites of TFDG. Glucuronidated and sulfated, instead of methylated metabolites of theaflavin 3-gallate, theaflavin 3′-gallate, and TFDG were detected and identified as the minor mouse fecal metabolites of TFDG. Our results indicate that TFDG can be degraded in mice. Further studies on the formation of those metabolites in TFDG-treated mice in germ-free conditions are warranted. To our knowledge, this is the first report on the biotransformation of TFDG in mice.